A comparative study of 8-week complex training and resistance training on athletic performance of amateur futsal players - Zhai, Yuan; Qin, Guoyang (Frontiers in Physiology, 2024)
Background: Despite the acknowledged importance of resistance training (RT) in enhancing physical performance in futsal players., the comparative effectiveness of RT and complex training (CT) on both physical and technical performance in futsal players remains underexplored. This study aimed to compare the effects of RT vs. CT on physical and technical performance in amateur futsal players.Method: Players from two amateur futsal teams were assigned to RT (one team of 16 players; 18 years) and CT (one team of 16 players; 18 years) to perform an 8-week intervention with two weekly sessions. The RT performed the squat and deadlift (6 sets of 6-10 repetitions at 75-85% onerepetition maximum (1RM), while the CT performed the squat + squat jump and deadlift + high pull (3 sets of 4-6 + 10-12 repetitions at 75-85% 1RM). Pre-and post-intervention assessments included the Futsal Special Performance Test (FSPT), repeated sprint ability (RSA), sprint decrement (Sdec), sprint times at 10-m (T10), 10-20-m (T10-20), and 20-m (T20), 1RM back squat (1RM BS), isometric mid-thigh pull (IMTP), and countermovement jump (CMJ).Results: At baseline, no significant differences between groups were observed for any variable analyzed (p > 0.05). After eight weeks, there were significant differences between CT vs. RT on FSPT (-10.8% vs. -3.4%; p < 0.05), T10 (-5.2% vs. -0.1%; p < 0.05), IMTP (7.8% vs. 5.1%; p < 0.05), and CMJ (10.2% vs. 4.5%; p < 0.05). On the other hand, no significant differences between CT vs. RT were observed for RSA (-2.0% vs. -1.2%; p > 0.05), Sdec (-7.6% vs. -3.5%; p > 0.05), T10-20 (-0.9% vs. -0.9%; p > 0.05), T20 (-1.8% vs. -1.7%; p > 0.05), and 1RM BS (5.7% vs. 4.5%; p > 0.05) after the training program. Both groups significantly improved FSPT, T20, 1RM BS, and IMTP, while only CT significantly improved RSA, Sdec, T10, and CMJ.The results suggest that CT may be valuable for improving specific performance parameters in amateur futsal players, with some advantages over RT in enhancing strength and power. These findings support tailored training protocols for futsal players to optimize performance.